2010
DOI: 10.1523/jneurosci.0511-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Meningeal Nociceptors by Cortical Spreading Depression: Implications for Migraine with Aura

Abstract: Attacks of migraine with aura represent a phenomenon in which abnormal neuronal activity in the cortex produces sensory disturbances (aura) some 20 -40 min before the onset of headache. The purpose of this study was to determine whether cortical spreading depression (CSD)-an event believed to underlie visual aura-can give rise to activation of nociceptors that innervate the meninges-an event believed to set off migraine headache. CSD was induced in anesthetized male rats by stimulation of the visual cortex wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
324
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(343 citation statements)
references
References 41 publications
12
324
3
4
Order By: Relevance
“…9,10 Neuroimaging studies in humans indicate that CSD underlies the migraine aura; animal studies indicate that CSD may also trigger the migraine headache mechanisms. [11][12][13] To study the cortical mechanisms that produce facilitation of CSD in FHM1 mutant mice, we investigated cortical neurotransmission in neuronal microcultures and in brain slices from FHM1 KI ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Neuroimaging studies in humans indicate that CSD underlies the migraine aura; animal studies indicate that CSD may also trigger the migraine headache mechanisms. [11][12][13] To study the cortical mechanisms that produce facilitation of CSD in FHM1 mutant mice, we investigated cortical neurotransmission in neuronal microcultures and in brain slices from FHM1 KI ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Introductionmentioning
confidence: 99%
“…Cortical spreading depression is the electrophysiological manifestation of aura in the cerebral cortex thought to activate the trigeminovascular system and ultimately provoke headache. Controversy exists as to whether this process happens through CGRP release from peripheral trigeminal terminals [34,108,109]. Studies in rats showed endogenous release of CGRP during extracellular hyperkalemia-induced cortical spreading depression and inhibition of this phenomena by CGRP-RAs [110].…”
Section: Migraine and Auramentioning
confidence: 99%
“…Such neurogenic inflammation is thought to trigger a headache via stimulation of trigeminal afferents. Consistent with this hypothesis, cortical SD induced intracranial neurogenic inflammation around the meningeal blood vessels [13][14][15] , and subsequent activation of both peripheral [16] and central [17] trigeminal nociceptive pathways has been described. Here, we review the experimental evidence mainly from neurophysiological studies that has advanced the understanding of whether and how the neurovascular phenomenon of cortical SD causes intracranial neurogenic inflammation, and subsequently participates in triggering a migraine headache.…”
mentioning
confidence: 55%